TMJ online: Investigating temporomandibular disorders as "TMJ" on YouTube. (24th October 2017) - Basch, C. H.; Yin, J.; Walker, N. D.; de Leon, A. J.; Fung, I. C.‐H.
Summary: As the understanding of temporomandibular disorders' (TMDs) aetiologies and treatments develops from non‐evidence‐based to evidence‐based approaches, the availability of sound information will likewise grow and need to be disseminated. The purpose of this study is to describe the content most commonly viewed in YouTube videos related to TMDs or "TMJ" and see whether videos from different sources have different content. Video information was gathered by searching YouTube for the term "TMJ, " and data were recorded related to descriptive information as well as content. Statistical analyses included Kruskal‐Wallis H Test, Spearman's Rho and univariate logistic regression. The sources of upload were Consumer (n = 62), Professional (n = 29) and News (n = 9). There were almost no statistically significant differences in content distribution among video sources. Videos garnered a total of 4 749 360 views, with an overall median of 7014.5 views. About two‐thirds of the videos (68/100) explained what "TMJ" is, with a surprising third of Professional videos (9/29) not covering the subject. Roughly half of the videos mentioned at least one reason "TMJ" occurs (55/100), and seven in ten mentioned some kind of treatment (70/100). Video names mentioned a cure or treatment in 64 cases, while the other 36 referred to TMJ anatomy or "TMJ" aetiology. Future research should focus on ways to popularise professional videos with reliable information for those who are searching on YouTube for advice related to "TMJ."